2018
DOI: 10.1093/tbm/ibx045
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and behaviors of health professionals towards smoking cessation in primary healthcare settings

Abstract: This study aimed to assess the behaviors of multiple health professionals in primary healthcare settings in Jordan towards smoking cessation counseling and to determine the barriers to effective smoking cessation behaviors. A survey of 456 health professionals in primary healthcare settings was conducted. A self-administrated questionnaire was used to collect the data. About half of health professionals reported that they usually ask patients about smoking status and advise them to stop smoking (51.4% and 50.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 21 publications
4
23
2
Order By: Relevance
“…Nevertheless, guidelines recommend the delivery of all the 5As, irrespective of whether smokers are motivated to quit or not 6 . Unlike what was reported in some studies 24,[26][27][28] , doctors in our study did not outperform the other healthcare professionals in all the 5As. Nonetheless, doctors were more likely to have counselled an increased number of patients, than other professionals during the previous week.…”
Section: Reflection On Main Findings and Highlights From The Literaturecontrasting
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, guidelines recommend the delivery of all the 5As, irrespective of whether smokers are motivated to quit or not 6 . Unlike what was reported in some studies 24,[26][27][28] , doctors in our study did not outperform the other healthcare professionals in all the 5As. Nonetheless, doctors were more likely to have counselled an increased number of patients, than other professionals during the previous week.…”
Section: Reflection On Main Findings and Highlights From The Literaturecontrasting
confidence: 99%
“…The inconsistent delivery of all of the 5As was acknowledged in international literature [24][25][26][27][28] . A similar trend in the delivery of the 5As was reported in a study amongst hospital health workers in Catalonia, Spain 26 .…”
Section: Reflection On Main Findings and Highlights From The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was constructed after an extensive literature review. [2,7,[13][14][15]] Some of its domains were taken from pre-validated tools which were adopted with the permission of corresponding authors. [7,16] To ensure validity and reliability of the tool, a pilot study and pre-testing of the questionnaire was conducted using a sample of 20 PHC physicians'.…”
Section: Methodsmentioning
confidence: 99%
“…A finding that was also evaluated among 456 PC professionals in Jordan, which showed that 51.4% asked about smoking and 50.5% advised cessation. Nevertheless, only 23.7% evaluated willingness to give up smoking, and a mere 17.9% explained different counselling options 21 .…”
Section: Comparison With Other Studiesmentioning
confidence: 99%